If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 11 = n + -7 Reorder the terms: 11 + 4n = n + -7 Reorder the terms: 11 + 4n = -7 + n Solving 11 + 4n = -7 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 11 + 4n + -1n = -7 + n + -1n Combine like terms: 4n + -1n = 3n 11 + 3n = -7 + n + -1n Combine like terms: n + -1n = 0 11 + 3n = -7 + 0 11 + 3n = -7 Add '-11' to each side of the equation. 11 + -11 + 3n = -7 + -11 Combine like terms: 11 + -11 = 0 0 + 3n = -7 + -11 3n = -7 + -11 Combine like terms: -7 + -11 = -18 3n = -18 Divide each side by '3'. n = -6 Simplifying n = -6
| X+8=4-2(3x+1) | | y-7=5 | | 28a-5a^2-3a^3=0 | | 6(x-1)=30 | | -140-10x=8x+22 | | 38=2.5a | | 7x+42=10x | | 12=2d+32 | | -3-3=4-3x+4x | | 4x-13=-78-9x | | 4.8x=-9.3-1.7x | | 82-3X=3X+16 | | 32=4g | | 2(m+4)+3(m-5)=8 | | -5w+2+6w=4+9 | | 3x-(2x)= | | 227-6x=30x+23 | | 8(2h+6)=12h+20 | | 4n^2+8n-140=0 | | 12-10x=107-45x | | 93-4x=23x+21 | | 8-8x=153-43x | | 2x+6=-27-9x | | 3(3x+4)-2x-5-7x=20 | | 6b^2+24b-192=0 | | 29*3= | | -2[4(k-2)-3(k+1)]=14+2k | | 3r^2=4r-1 | | 8y^2+17y+2=0 | | 4m^2-8m-192=0 | | 14t-28=7(t+6) | | 7x+42+4x+6=180 |